1984
DOI: 10.1038/icb.1984.23
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Bronchodilator Action of Verapamil

Abstract: Summary Although calcium antagonists such verapamil are used primarily in cardiovascular disease, they appear to relax smooth muscle generally. Therefore, the possibility that verapamil might have bronchodilator properties was explored using the guinea‐pig tracheal ring technique. Verapamil was found to produce considerable tracheal smooth muscle relaxation from a threshold concentration of 2 × 10−7M and with maximum effect at 10−3M. The responses to the contractile agonists histamine and prostaglandin F2α and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…[ 20,21 ] Being biocompatible and biodegradable, CR and its derivatives have been extensively investigated in biomedical applications like vasodilatative, hypoglycemic, bacteriostatic, analgesic, and anticonvulsant effects. [ 22–25 ] It has also been studied in biochemical and functional studies. [ 26,27 ] Shafi Ullah et al [ 28 ] have reported the biocompatibility of a novel creatinine‐based non‐ionic surfactant LC‐CRT and its use in niosomal drug delivery and the effective sensor for selective potentiometric detection of the creatininium cation (2H + ) in body fluids have been reported by Toms Guinovart et al [ 29 ] Cocrystals of creatinine with benzoic acid and salicylic acid have been synthesized by Goswami et al [ 30 ] The 1:1 proton‐transfer compounds of creatinine with a series of aromatic carboxylic acids have been reported by Smith et al The mononitro‐substituted benzoic acids are 3,5‐dinitrobenzoic acid, 5‐nitrosalicylic acid, 3,5‐dinitro salicylic acid, and pyrazine‐2,3‐dicarboxylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20,21 ] Being biocompatible and biodegradable, CR and its derivatives have been extensively investigated in biomedical applications like vasodilatative, hypoglycemic, bacteriostatic, analgesic, and anticonvulsant effects. [ 22–25 ] It has also been studied in biochemical and functional studies. [ 26,27 ] Shafi Ullah et al [ 28 ] have reported the biocompatibility of a novel creatinine‐based non‐ionic surfactant LC‐CRT and its use in niosomal drug delivery and the effective sensor for selective potentiometric detection of the creatininium cation (2H + ) in body fluids have been reported by Toms Guinovart et al [ 29 ] Cocrystals of creatinine with benzoic acid and salicylic acid have been synthesized by Goswami et al [ 30 ] The 1:1 proton‐transfer compounds of creatinine with a series of aromatic carboxylic acids have been reported by Smith et al The mononitro‐substituted benzoic acids are 3,5‐dinitrobenzoic acid, 5‐nitrosalicylic acid, 3,5‐dinitro salicylic acid, and pyrazine‐2,3‐dicarboxylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Forty years ago John Cade brought lithium into modern medicine (1) as one of the important drugs in the management of affective disorders. This makes lithium the oldest psychotropic drug still in use, outlasting chlorpromazine (LargatiP) by 3 years.…”
mentioning
confidence: 99%